Comparative evaluation of efficacy of calcium silicophosphate putty versus particulate xenograft in maxillary sinus augmentation procedure: A clinical and tomographical study - Dushyant Malik; Mohinder Panwar; Manab Kosala; Jacqueline Jacinta Dias (Wolters Kluwer Medknow Publications, 2018)
Introduction: Remodeling of bone and pneumatization of maxillary sinus posttooth extraction results in loss of residual bone height in maxillary posterior segment. Hence, maxillary sinus elevation procedure is a commonly practiced procedure for the placement of dental implant in maxillary posterior region with inadequate residual bone. Various graft materials are being used in the space created after elevation of sinus membrane to maintain sinus lining in place and formation of new bone. Aim and Objective: The aim of this study is to compare efficacy of calcium silicophosphate putty and particulate xenograft material in direct maxillary sinus elevation procedure, clinically as well as tomographically. Materials and Methods: Twenty patients with the residual alveolar bone height between 3.5 and 6.5 mm in the edentulous maxillary posterior region requiring direct maxillary sinus lift were selected for the study and divided into two groups. In Group A, calcium silicophosphate putty (NovaBone® Dental Putty) was used as graft material and in Group B, particulate xenograft (Bio-Oss®) was used. In both the groups, simultaneous implant placement was done after maxillary sinus elevation. Patients were assessed radiographically (cone-beam computed tomography) after a period of 6 months for increase in bone height and density of new bone formed. Results: The mean increase in bone height postsinus elevation was found to be statistically significant with xenograft (9.8 ± 1.21 mm). It was also found that the new bone formed postsinus elevation was much more denser than existing bone in cases where xenograft was placed in cavity postsinus membrane elevation (759 ± 211 Hounsfield unit). Conclusion: All the implants placed were successfully rehabilitated. Statistically significant difference was observed an increase in bone height and density of new bone formed with xenograft.